Lectures on legal language and legal writing - Rao, Rega Surya (Hyderabad, 2008)
The subject, "Legal Language and Legal Writing" was one of the subjects prescribed for the second year of Five Year B.L/LL.B. Course earlier. The Bar Council of India restructured the curriculum B.L/LL/B. Course from the academic year 1998-99 and pre scribed the Legal Language and Legal Writing as one of the subjects for the first year of 3 Year B.L./LL.B. Course and 3rd year of 5 Year B.LLL.B. Course. The subject is of great importance, since it enlightens the student on various branches of Law in brief and the drafts of various deeds and other documents pertaining to the legal profession. It comprises of two parts, namely: (1) Legal Language; and (2) Legal Writing. The first part deals with Law in general, covering various branches of Law in brief, while the second part deals with various aspects viz. conveyancing, deeds, pleadings, legal maxims, translation etc.
Keywords: Legal language-Lectures